World without end - Follett, Ken (Follett, Ken. Kingsbridge series., 2007)
Two centuries after the building of the elaborate Gothic cathedral in Kingsbridge, its prior finds himself at the center of a web of ambition and revenge that places the city at a crossroad of commerce, medicine, and architecture.